Dampak Media Sosial terhadap Usaha Kecil dan Menengah (UKM) Sentra Industri Keramik Plered, Kabupaten Purwakarta - Danang Sanggabuwana; Susi Andrini (Inter Komunika, 2017)
Abstract .The development of social media makes it recommended that social media become the most important part in developing and advancing its business especially in the field of promotion, marketing and marketing as a whole. The existence of today's social media applications has become the most efficient and effective tool for ceramic SMEs in Ceramic Plered Industrial Center, Purwakarta District, and today most of the SMEs have followed the digital era by using social media platform for marketing communications, advertisement, product publicity ceramics and services they provide. They create fan pages for followers to make communication fast, even in different cities or countries SME ceramic actors can warmly welcome advice and opinions that help in improving their business. Based on the review that there is a positive impact although there is also a negative impact of social media applications on the development of business SMEs ceramic entrepreneurs but not undo the intention to advance its business, and motivated to use this platform.Keywords: media, social media